SMART-In English: Learn English Using Speech Recognition - Dhanar Intan Surya Saputra; Sitaresmi Wahyu Handani; Kuat Indartono; Andik Wijanarko (Universitas Muhammadiyah Yogyakarta, 2020)
English is an international language and important to learn. For someone learning English sometimes is a difficulty, especially in pronunciation. Therefore, SMART-In is a prototype of Android App that uses Speech Recognition technology by utilizing services from the Cloud Speech API (Application Programming Interface). SMART-In English can be used as an alternative to English learning, especially in the pronunciation of a word. Using speech recognition can display the score of the pronunciation spoken by the user, recorded, show a level the pronunciation of the word and display the correct pronunciation.